The Effect of Project Based Learning (PjBL) Model on Students' Science Literacy in Social Studies Subjects (Jurnal Penelitian dan Pengkajian Ilmu Pendidikan: e-Saintika, 2022)
This study aims to analyze the effect of the project-based learning (PjBL) model on students' scientific literacy and to describe the effect of the PjBL model on students' scientific literacy in Social Science subjects with the theme of fire disaster mitigation in residential areas. The research design used in this study is a one-group pretest-posttest design using a quantitative approach the population is 496 students, and the sample size is 60 students with a purposive sampling technique. The location of this research is SMK Negeri 1 Lamongan. The data collection technique in this study used a scientific literacy test and an observation sheet on the implementation of learning then the data analysis technique applied in this study used a feasibility test of learning instruments and tools, namely the Lesson Plan (RPP) validation test, Student Worksheet (LKPD), and scientific literacy test, then a prerequisite test was carried out namely normality, and homogeneity tests were then tested using a paired sample t-test to measure students' scientific literacy and to measure learning implementation sheets using learning implementation analysis. The results of this study shows that (1) the implementation of learning in lesson plans using PjBL is in the very good category with an average of 91.19%; (2) PjBL model has significant effect on students' scientific literacy (p <0.05). Therefore, it can be concluded that there is a significant effect between the PjBL model on students’ scientific literacy and the implementation of RPP using the PjBL model is in the very good category.